2018
DOI: 10.1101/489302
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A reevaluation of the electrophysiological correlates of absolute pitch and relative pitch: No evidence for an absolute pitch-specific negativity.

Abstract: Musicians with absolute pitch effortlessly identify the pitch of a sound without an external reference.Previous neuroscientific studies on absolute pitch have typically had small samples sizes and low statistical power, making them susceptible for false positive findings. In a seminal study, Itoh et al. (2005) reported the elicitation of an absolute pitch-specific event-related potential component during tone listening -the AP negativity. Additionally, they identified several components as correlates of relati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In EEG, this interference is reflected by a negative-going deflection around 400 ms after target-onset, which is referred to as the N400 (Kutas and Hillyard 1980;Zhang et al 2010). EEG has an excellent time resolution and has been insightful in capturing the early perceptual and cognitive processes underlying AP (Elmer et al 2013;Rogenmoser et al 2015;Greber et al 2018;Burkhard et al 2019;Leipold, Oderbolz, et al 2019). In the present study, the participants were instructed to judge as quickly and accurately as possible whether pictures (targets) were either pleasant or unpleasant by pressing one of two response buttons.…”
Section: Introductionmentioning
confidence: 99%
“…In EEG, this interference is reflected by a negative-going deflection around 400 ms after target-onset, which is referred to as the N400 (Kutas and Hillyard 1980;Zhang et al 2010). EEG has an excellent time resolution and has been insightful in capturing the early perceptual and cognitive processes underlying AP (Elmer et al 2013;Rogenmoser et al 2015;Greber et al 2018;Burkhard et al 2019;Leipold, Oderbolz, et al 2019). In the present study, the participants were instructed to judge as quickly and accurately as possible whether pictures (targets) were either pleasant or unpleasant by pressing one of two response buttons.…”
Section: Introductionmentioning
confidence: 99%
“…Also, if AP possessors achieved much higher naming accuracy than non‐possessors, the observed neural differences between AP and non‐AP possessors may be alternatively explained by their different levels of attentional engagement (Liu et al, 2016; Philiastides et al, 2006). Finally, some studies did not include any control stimulus category to control for potential group differences in general auditory processing, and therefore the observed neural differences could reflect differences in auditory processing between AP and non‐AP possessors that were non‐specific to AP (e.g., Barnea et al, 1994; Hirose et al, 2003, 2004; Itoh et al, 2005; Leipold, Oderbolz, et al, 2019; Wu et al, 2008). To clarify the neural mechanisms of AP, it is important to adopt an experimental design that can adequately address these methodological issues.…”
Section: Introductionmentioning
confidence: 99%
“…However, a larger N1 among AP possessors was not found in other studies that also employed listening and labeling conditions, such as (Hirose et al, 2003) for children and (Elmer et al, 2013) for adult musicians. Itoh et al (2005) identified a negative component at 150 ms right after the N1 that was unique to AP possessors, but Leipold, Oderbolz, et al (2019) failed to find it in a direct replication. For the P2, larger P2 activation in AP possessors was observed in response to vocal pitch deviation (Behroozmand et al, 2014) and passive listening (Wengenroth et al, 2014).…”
Section: Introductionmentioning
confidence: 99%